Functional Characterization of Sex Pheromone Neurons and Receptors in the Armyworm, Mythimna separata (Walker) - Wang, Chan; Wang, Bing; Wang, Guirong (Frontiers in Neuroanatomy, 2021)
Pheromone receptors (PRs) of moths are expressed on the dendritic membrane of odorant receptor neurons (ORNs) housed in the long trichoid sensilla (TS) of antennae and are essential to sex pheromone reception. The function of peripheral neurons of Mythimna separata in recognizing sex pheromones is still unclear. In this study, electroantennogram (EAG) recordings were performed from male and female antennae of M. separata, and showed that the major component of sex pheromones, (Z)-11-hexadecenal (Z11-16:Ald), evoked the strongest response of male antennae with significant differences between sexes. Single sensillum recording (SSR) was used to record responses of neurons housed in TS of male M. separata. The results revealed four types of TS with three neurons housed in each type, based on profiles of responses to sex pheromone components and pheromone analogues. ORN-B of type-I TS was specifically tuned to the major sex pheromone component Z11-16:Ald; ORN-Bs in type-III and type-IV TSs were respectively activated by minor component (Z)-11-hexadecen-1-yl acetate (Z11-16:OAc) and hexadecenal (16:Ald); and ORNs in type-II TS were mainly activated by the sex pheromone analogues. We further cloned full-length sequences of six putative PR genes and an Orco gene. Functional characterization of PRs in the Xenopus oocyte system demonstrated that male antennae-biased MsepPR1 responded strongly to (Z)-9-tetradecenal (Z9-14:Ald), suggesting that MsepPR1 may be expressed in type-II TS. MsepPR6 was exclusively tuned to (Z)-9-tetradecen-1-yl acetate (Z9-14:OAc). MsepPR2 and MsepPR4 showed no responses to any tested components. Female antennae-biased MespPR5 was broadly tuned to Z9-14:Ald, Z9-14:OAc, Z11-16:Ald, and (Z)-11-hexadecen-1-ol (Z11-16:OH). Our results further enriched the sex pheromone recognition mechanism of the peripheral nervous system in moth M. separata.